Clinical use of liquid biopsy in metastatic breast cancer: an ESSO-EYSAC international survey - Suppan, Ina; Lundon, Dara; Garg, Pankaj Kumar; Caballero, Carmella; Heitzer, Ellen; Brandl, Andreas (Journal of surgical oncology, 2025)
IntroductionAlthough recommendations for using Liquid Biopsy (LB) approaches to guide therapeutic decisions in metastatic breast cancer (mBC) have been embedded in various guidelines, uptake in clinical practice is slow. Here, we aimed to assess the utilization and key issues for implementation of LB across Europe.Materials and MethodsUsing the Redcap platform, we developed an online questionnaire including nineteen questions investigating three principal areas: respondent demographics; awareness, knowledge, and access to LB approaches; as well as future perspectives of LB. The survey was distributed to networks of surgical oncologists, via email, social media, and the ESSO-EYSAC website from March 2023 to May 2023.ResultsA total of 292 breast cancer experts from 39 different countries completed the survey. Only 58 participants (20%) reported implementation of guidelines regarding LB testing. Overall, 119 participants (40.7%) indicated current use of liquid biopsy. The top three indications for LB utilization were "clinical studies" (n = 107, 36.8%), the "evaluation of therapeutic possibilities" (n = 109, 37.5%) and "prognostication" (n = 59, 20.3%). The major reasons for not using LB testing in the treatment of mBC patients were high costs and lack of reimbursement (n = 133, 38.7%) followed by lack of access (n = 126, 36.6%) and lack of evidence of the clinical utility (n = 62, 18.0%).ConclusionLB testing is slowly becoming more popular in clinical practice, but still faces major difficulties such as high costs, and lack of reimbursement. More evidence is needed to show that individualization of treatment by utilization of LB leads to better outcome in mBC patients.